Алгоритм визначення станів рівноваги за умови залежності структури споживання від обсягів випуску - Makhort, Andrii P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
The model describes an economy with monopolies and consumers interests dependent on the production volume of goods. Determined limitations of defined model characteristics prove an equilibrium existence. The equilibrium existence means a solvability of equilibrium equations. An algorithm for solving the equilibrium problem is propoіsed. Each solution corresponds to an equilibrium state of the economy. The algorithm determines the equilibrium states with indicated properties. Discovered optimal values of equilibrium characteristics guarantee an acceptable level of satisfaction of all economy subjects' needs. Evaluated boundary values of equilibrium characteristics lead to an estimation of an attainment of selected equilibrium states.